Vida, autoridad, desengaño y burla en la poesía de Bances Candamo - Oteiza, Blanca (Hipogrifo: Revista de Literatura y Cultura del Siglo de Oro, 2020)
In this article, the author relates the authority of Bances with his poetic models and the derision of some motifs and literary styles. This shows interesting relations between his life and literature, that can be easily found in his lyric work.